THE ROLE OF BALADA CENDERAWASIH TRADITIONAL DANCE OF PAPUA - Sri Winarsih (British : Jurnal Bahasa dan Sastra Inggris, 2020)
Balada Cenderawasih is a traditional dance of Papua which is performed by a group of dancers in the costumes resembling beautiful Paradise birds. The dance is often performed in many important events in Merauke. This study aims to find out the role of Balada Cencerawasih as a kind of ballad from Papua beyond an art show. Two subjects were studied; the dance and the owner of traditional dance studio. Through overt observation over the dance, and semi structured interview with the owner of traditional dance studio, it was collected the data and were analyzed using Spradley qualitative model. The study shows the roles of Balada Cenderawasih are as; 1) Cultural identity; through the motions, language and symbols; 2) Regional wealth, both material and cultural heritage; through the show includes costumes, musical instruments and the dancer attributes; and 3) Environmental protection; through the values include moral, religious and education.Keywords: balada cenderawasih, ballad, role, traditional dance